An exploratory study of neopterin and kynurenine pathway in pterygium - Kilicarslan Bilge; Cardak Aziz; Girgin Gozde; Kemer Ozlem Evren; Baydar Terken (Pteridines, 2019)
Pterygium is an inflammatory, vascular and degenerative disorder with unknown aetiology. The aim of this study was to evaluate the changes in neopterin levels, reflecting T-cell immunity, and the kynurenine pathway, the main degradation process of tryptophan, in pterygium. For this purpose, neopterin concentrations were measured in serum and tear samples by enzyme-linked immunosorbent assay (ELISA) in pterygium patients (n=31) and control group (n=32). Kynurenine (KYN) and tryptophan (TRP) serum levels were simultaneously determined by high-performance liquid chromatography (HPLC) for evaluation of the kynurenine pathway. Serum neopterin concentrations and kynurenine to tryptophan ratio (KYN/TRP) as an index of tryptophan breakdown were found increased in pterygium compared to controls (p<0.05). Although there was a 3-fold difference observed between serum and tear neopterin levels, no significant relationship was found. It can be concluded that neopterin may be used as a nonspecific biomarker that reflects immunological activity in pterygium and has clinical potential for evaluation of pterygium pathogenesis. These immune- or inflammatory-mediated changes were also supported by an increased KYN/TRP ratio in pterygium patients.